Integrating sensory assessments in preventive home visits: a cross-sectional study of the Faroe Islands - Haanes Gro Gade; Tor Martin Kvikstad; Ása Roin (International Journal of Circumpolar Health)
Background: Sensory impairments, including hearing and vision loss, are common in older adults and can affect quality of life. This study examines the integration of hearing and vision assessments in preventive home visits (PHVs) for older adults in the Faroe Islands, comparing outcomes between urban and rural settings.Aim: To evaluate the feasibility of including sensory assessments in PHVs and compare sensory measurements between Tórshavn (urban) and rural districts.Methods: A cross-sectional study with 175 participants aged 76 was conducted in Tórshavn and five rural areas. Data included demographics, self-assessments, and clinical evaluations using standardized tools.Results: Visual impairments were slightly more prevalent in rural areas, while hearing impairments showed no significant differences. Discrepancies between self-reported and measured impairments emphasized the importance of objective assessments. Sensory acreenings during PHVs improved early detection and highlighted inequities in access to specialized services.Conclusion: Integrating sensory assessments in PHVs is feasible and beneficial, adressing disparities between urban and rural areas. These screenings support equitable healthcare and early intervention, promoting better quality of life for older adults across diverse settings.